THE INFLUENCE OF FINANCIAL LITERACY, FINANCIAL EFFICACY, AND INVESTMENT KNOWLEDGE ON INVESTMENT INTEREST IN THE CAPITAL MARKET AMONG STUDENTS OF THE FACULTY OF ECONOMICS AND BUSINESS, AAS INDONESIA BUSINESS TECHNOLOGY INSTITUTE - Dela Setiarini; Suprihati; Agus Subekti (International Journal of Economics, Business and Accounting Research (IJEBAR), 2026)
This study aims to analyze the influence of financial literacy, financial efficacy, and investment knowledge on investment interest in the capital market among students of the Faculty of Economics and Business, AAS Indonesia Institute of Business Technology. This study used a quantitative method with a sample of 88 respondents and a sampling technique using Slovin. The data analysis technique used was multiple linear regression with the help of the SPSS program. The results showed that investment knowledge influenced investment interest, while financial literacy and financial efficacy did not. Simultaneously, the three independent variables influenced the dependent variable, namely investment interest. Thus, it can be concluded that the most dominant factor influencing investment interest is investment knowledge.